Optimal unequal phase steps for laser direct writing in DPE manufacturing - Mihailescu, Mona; Paun, Irina Alexandra; Scarlat, Eugen I; Mihale, Nicolae; Tranca, Denis; Calin, Bogdan Stefanita; Luculescu, Catalin Romeo (SPIE, 2018)
Various manufacturing techniques are used to minimize the number of micro--relief steps and consequently the time and volume of processed substance for large scale production of diffractive phase elements (DPEs) such that to approximate the desired field distribution in terms of mean squared error, uniformity, and efficiency in the lower domain of quantized phase levels. The paper presents a method to optimize DPE manufacturing using unequal imprinted phase steps by direct laser writing via two photon polymerization. The algorithm is implemented with Python software and contains two feedback loops of analysis: one at the optical image level, the other at the DPE level. The unequal sizes of phase steps are optimal with respect to the particular DPE subjected to fabrication. DPEs and the corresponding optical images are presented in simulated and experimental versions, respectively. The results are evidencing the advantage of unequal steps versus the equal ones. The method is an acceptable compromise between preserving relevant micro-relief details and accurate image reconstruction under the constraint of limited number of imprinted steps and lower processing time.